The Effectiveness Of Social Media Campaigns On Boycott Participation: The Role Of Boycott Attitudes And Motivation - Leni Susanti; Weni Novandari; Refius Pradipta Setyanto (International Journal of Economics, Business and Innovation Research, 2024)
The efficacy of boycotting brands and companies that affiliate with some issues as a form of nonviolent protest has been subject to growing scrutiny due to several issues impacting the individuals and groups engaged in these movements. This research aims to investigate and ascertain the purchase intention among Indonesian consumers regarding their participation in boycott activities following the global call to boycott products. The population in this study are students who actively use social media and find information about boycotts. A sample of 100 students was used as respondents. SmartPLS version 3 is used as an analysis tool. The survey in this study examines the correlation between seven constructs in the context of the boycott issue through the use of questionnaires. The findings indicate that social media campaigns have no discernible impact and are not significant in influencing purchase intention. And the rest constructs have effect and significant to purchase intention.